(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions defined from an ideal topological space into a bitopological space, called upper weakly τ^(σ_1,σ_2)-continuous multifunctions and lower weakly τ^(σ_1,σ_2)-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper weakly τ^(σ_1,σ_2)-continuous multifunctions and lower weakly τ^(σ_1,σ_2)-continuous multifunctions are investigated. Moreover, the relationships between almost τ^(σ_1,σ_2)-continuity and weak τ^(σ_1,σ_2)-continuity are established.